Hepatoprotective effect of Alhagi sparsifolia against Alcoholic Liver injury in mice (Brazilian Journal of Pharmaceutical Sciences, 2018)
Overconsumption of alcohol leads to alcoholic liver disease (ALD). Natural compounds have been investigated previously for their hepatoprotective activities against liver injury. This study investigated the protective effect of Alhagi sparsifolia on ALD. Alcohol was administered to mice for three consecutive days; either alone or in combination with Alhagi sparsifolia extract (150, 300, 600 mg/kg). Serum aspartate aminotransferase and alanine transaminase as biomarkers of liver injury, the content of malonaldehyde, hydrogen peroxide (H2O2) and glutathione which indicated the redox status of liver and the antioxidant enzyme activity of super oxide dismutase were detected, respectively. Moreover, the expression of protein cytochrome P450 2E1 (CYP2E1) the key enzyme of alcohol metabolism, and also tested by western blot experiment. Subsequently, the mRNA levels of inflammatory factors including TNF- α and TLR4 was determined real-time PCR. Results showed that Alhagi sparsifolia significantly alleviated alcohol-induced liver injury by reducing serum ALT and AST, inhibiting MDA and H2O2 content, increasing SOD, and GSH level in the liver (P< 0.05). In addition, the Alhagi sparsifolia treatment inhibited the expression of CYP2E1 (P< 0.05). The results suggest that Alhagi sparsifolia could be a promising natural substance for ameliorating acute alcohol-induced oxidative stress and hepatic injury.